2010
DOI: 10.1093/cvr/cvq339
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1 inhibition promotes in vivo arterial thrombosis and tissue factor expression in stimulated cells

Abstract: We provide pharmacological and genetic evidence that Sirt1 inhibition enhances TF expression and activity by increasing NFκB/p65 activation in human endothelial cells. Furthermore, Sirt1 inhibition induces arterial thrombus formation in vivo. Hence, modulation of Sirt1 may offer novel therapeutic options for targeting thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 49 publications
2
81
0
1
Order By: Relevance
“…While we did not investigate the exact transcriptional machinery engaged by mitochondrial NADH shuttling, we demonstrate using two different cell types that increased SIRT1 expression occurs during physiologic Ca 2ϩ signaling and SIRT1 upregulation is linked to a mitochondrion-directed decrease in the cytosolic NAD ϩ /NADH ratio. Endothelial SIRT1 targets multiple proteins to effectively modulate nitric oxide production (75,76), inflammation (47,77,78), and vessel growth (79,80). Thus, SIRT1 expression is widely considered a positive effector of EC function.…”
Section: Discussionmentioning
confidence: 99%
“…While we did not investigate the exact transcriptional machinery engaged by mitochondrial NADH shuttling, we demonstrate using two different cell types that increased SIRT1 expression occurs during physiologic Ca 2ϩ signaling and SIRT1 upregulation is linked to a mitochondrion-directed decrease in the cytosolic NAD ϩ /NADH ratio. Endothelial SIRT1 targets multiple proteins to effectively modulate nitric oxide production (75,76), inflammation (47,77,78), and vessel growth (79,80). Thus, SIRT1 expression is widely considered a positive effector of EC function.…”
Section: Discussionmentioning
confidence: 99%
“…3). 83 In vitro, SIRT1 diminishes tissue factor expression by deacetylating RelA/p65 and suppressing NFκB signaling in HAECs. SIRT1 inhibition or siRNA-mediated SIRT1 silencing in HAECs stimulated with inflammatory mediators increased tissue factor expression.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Zeng et al reported that SIRT1 knockdown induced hepatic inflammation by increasing the activation of NF-κB [40]. Breitenstein et al reported that SIRT1 inhibition enhanced NF-κB activation via acetylation of Lys310 NF-κB /p65 in human aortic endothelial cells [41]. To investigate the effect of SIRT1 deletion on NF-κB in HUVECs, we only silenced SIRT1 expression via transfection of SIRT1 siRNA and then evaluated p65 expression in both cytosol and nuclear fractions.…”
Section: Discussionmentioning
confidence: 99%